The Effect of Literacy Tree Media on Student Reading Interest in Indonesian Language Subjects Grade 4 SDN 1 Tigajuru Mayong - Diana Ragil Saputri; Dwiana Asih Wiranti (Green Publisher Indonesia, 2024)
This study aims to examine the effect of using Literacy Tree media on students' reading interest in Indonesian language subjects in grade 4 of SDN 1 Tigajuru Mayong. The method used in this study was a pseudo-experiment with a pretest-posttest design. The research sample consisted of 30 randomly selected 4th grade students. Data were collected through reading interest questionnaire and analyzed using t test to determine the difference in reading interest before and after using Literacy Tree media. The results showed that there was a significant increase in students' reading interest after using the Literacy Tree media. This finding indicates that the Literacy Tree media is effective in increasing students' reading interest in Indonesian language subjects. The implication of this study is the importance of using innovative and interesting learning media to increase students' interest in reading